6 - Tension Between Massification and Intensification Reforms and Implications for Teaching and Learning in Ethiopian Public Universities - Solomon Areaya (Journal of Higher Education in Africa, 2010)
This paper critically examines the context under which public universities are implementing series of predominantly government initiated and controlled reforms. Accordingly, it attempts to unpack those political, professional, and epistemological factors contributing to the decline of the quality of teaching and learning. Focus group discussions, official government documents and views, proclamations, pertinent national and international studies, informal discussions with university colleagues, and personal experiences have been used as sources of evidence to inform my analysis and discussion. The study revealed that the current educational environment in most public universities is messy and the quality of teaching and learning are at risk. Excessive intervention by the federal Ministry of Education and lack of autonomy seem the prime factors contributing to substandard outputs of the universities. A tension has been created between government’s political desire for massification of higher education on one hand, and the inherent desire of the universities and their academic communities for quality education by way of academic intensification on the other hand. Accordingly, the quality of teaching and learning in Ethiopian public universities currently is at risk.